Ruthenium monatomic alloy catalyst and plastic hydrogenolysis method
By using a ruthenium single-atom alloy catalyst to perform plastic hydrogenolysis at lower hydrogen pressure, the energy consumption and equipment technical challenges in the prior art under medium and high pressure conditions are solved, and the hydrogenolysis effect with high efficiency and low methane selectivity is achieved.
Patent Information
- Application Number
- CN202410716601.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-04
- Publication Date
- 2025-04-25
AI Technical Summary
The prior art requires high pressure conditions during the plastic hydrogenolysis process to inhibit methane generation, resulting in energy consumption and equipment technical challenges, making it difficult to achieve efficient and low methane selective hydrogenolysis at lower hydrogen pressures.
Using a ruthenium single atom alloy catalyst, a RuSAM type catalyst is formed by dispersing ruthenium single atom alloy nanoparticles in the support, and a RuSAM type catalyst is used to perform plastic hydrogenolysis at lower hydrogen pressure.
Under wide hydrogen pressure range and low temperature conditions, efficient hydrogenation of plastics is achieved, the conversion rate is significantly improved, and the selectivity of methane is greatly reduced, avoiding continuous bond breaks to produce more methane.
Smart Images

Figure CN119869514A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a ruthenium single-atom alloy catalyst and a plastic hydrogenolysis method, belonging to the technical field of plastic hydrogenolysis. Background Art
[0002] In the field of plastic processing technology, catalytic conversion of plastics into monomers or more valuable products through chemical methods has been proven to be an effective green and environmentally friendly way to achieve efficient recycling of plastics.
[0003] At present, the main chemical methods for plastics recycling include hydrogenolysis, pyrolysis, cracking, oxidation, etc. Among them, hydrogenolysis is an efficient method that can obtain high-value chemicals (liquid fuels and chemical products) at relatively low temperatures, but it requires high pressure (1-6MPa) to suppress the generation of methane, resulting in a large amount of additional energy input consumption and equipment technology challenges.
[0004] Therefore, finding new catalysts that can efficiently and selectively hydrogenolyze methane at lower hydrogen pressures is a difficult problem that needs to be solved urgently. Summary of the invention
[0005] In order to solve the above technical problems, the purpose of the present invention is to provide a ruthenium single-atom alloy catalyst, which can realize the hydrogenolysis of plastics under lower hydrogen pressure.
[0006] The present invention also provides a plastic hydrogenolysis method based on the ruthenium single-atom alloy catalyst.
[0007] To achieve the above object, the present invention provides a ruthenium single-atom alloy catalyst, which comprises a ruthenium single-atom alloy and a carrier, wherein the general formula of the ruthenium single-atom alloy is: Ru SA M, wherein M is selected from one or a combination of two or more of Pt, Pd, Fe, Co, Ni, Cu, Zn, Mg, Ca, and Mn; preferably Pt and / or Co;
[0008] Among them, the value of SA is 0.01-1.
[0009] In the above-mentioned ruthenium single-atom alloy catalyst, preferably, based on the mass of the ruthenium single-atom alloy catalyst as 100%, the loading amount of the ruthenium single-atom alloy is 1wt%-50wt%; more preferably, 1wt%-20wt%, and further preferably, 5wt%-20wt%.
[0010] In the above-mentioned ruthenium single-atom alloy catalyst, preferably, the carrier is selected from one or a combination of two or more of a carbon-based carrier, a metal oxide carrier and a metal nanoparticle carrier; more preferably, the carbon-based carrier is selected from Norit, Ketjen Black, activated carbon (Vulcan), Black Pearl, acetylene black, carbon nanotubes, graphene, carbon nitride (gC 3 N 4 ), nitrogen-doped carbon, molybdenum carbide, iron carbide, etc., or a combination of two or more thereof; the metal oxide in the metal oxide carrier is selected from one or a combination of two or more thereof: cerium oxide, zinc oxide, aluminum oxide, zirconium oxide, magnesium oxide, molybdenum oxide, tungsten oxide, etc.; the metal in the metal nanoparticle carrier is selected from one or a combination of two or more thereof: platinum, gold, silver, ruthenium, rhenium, palladium, etc.
[0011] According to a specific embodiment of the present invention, the above-mentioned ruthenium single-atom alloy catalyst can be prepared by the following method:
[0012] Dispersing ruthenium single-atom alloy nanoparticles in a first solvent to obtain a first solution, and dispersing a carrier in a second solvent to obtain a second solution;
[0013] The first solution and the second solution are mixed, and then subjected to ultrasound, filtration and drying to obtain a ruthenium single-atom alloy catalyst.
[0014] According to a specific embodiment of the present invention, preferably, the particle size of the ruthenium single-atom alloy nanoparticles is 2nm-20nm.
[0015] According to a specific embodiment of the present invention, preferably, the ruthenium single-atom alloy nanoparticles are prepared by a liquid phase colloid method in oleylamine at 120°C.
[0016] According to a specific embodiment of the present invention, preferably, the first solvent is selected from toluene, n-hexane, chloroform, etc., or a combination of two or more thereof, and the second solvent is selected from toluene, n-hexane, chloroform, etc., or a combination of two or more thereof.
[0017] According to a specific embodiment of the present invention, preferably, the concentration of the first solution is 0.001 wt%-0.004 wt%, and the concentration of the second solution is 0.01 wt%-0.04 wt%.
[0018] According to a specific embodiment of the present invention, preferably, the ultrasonication time is 30 minutes to 1 hour.
[0019] The present invention also provides a plastic hydrogenolysis method, which is carried out using the above-mentioned ruthenium single-atom alloy catalyst; the plastic hydrogenolysis method comprises the following steps:
[0020] The plastic is mixed with the ruthenium single atom alloy catalyst and placed in a hydrogen environment for hydrogenolysis.
[0021] In the above-mentioned plastic hydrogenolysis method, preferably, the mass ratio of the plastic to the ruthenium single-atom alloy catalyst is 0.01-2.0 g: 4-40 mg.
[0022] The catalyst provided by the present invention can achieve hydrogenolysis of plastics under both high hydrogen pressure and low hydrogen pressure, that is, in the above-mentioned plastic hydrogenolysis method, preferably, the hydrogen pressure of the hydrogen environment is 0-6MPa or below 6MPa.
[0023] When hydrogenolysis of plastic is performed under hydrogen pressure, preferably, the hydrogen pressure of the hydrogen environment is lower than 1 MPa, such as normal pressure (0.1 MPa). The catalyst provided by the present invention can achieve hydrogenolysis of plastic under low hydrogen pressure, which is not achievable with existing catalysts.
[0024] In the above-mentioned plastic hydrogenolysis method, preferably, the temperature of the hydrogenolysis is 100°C-500°C, more preferably 100°C-400°C.
[0025] In the above-mentioned plastic hydrogenolysis method, preferably, the plastic includes one or a combination of two or more of low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), high-density polyethylene (HDPE), polypropylene (PP), polystyrene (PS), polyvinyl chloride (PVC), polyethylene terephthalate (PET), polylactic acid (PLA), polycaprolactone (PCL), polycarbonate (PC), nylon 66 (PA), polybutylene terephthalate (PBT), polyurethane (PVR), etc.
[0026] In the above-mentioned plastic hydrogenolysis method, preferably, the hydrogenolysis is carried out under solvent-free conditions.
[0027] In the above-mentioned plastic hydrogenolysis method, preferably, the hydrogenolysis is carried out under stirring, and the stirring rate is preferably 300-600r / min.
[0028] In the above-mentioned plastic hydrogenolysis method, preferably, the reaction time of the hydrogenolysis is 0.1-24 hours.
[0029] In the above-mentioned plastic hydrogenolysis method, preferably, the hydrogenolysis can be carried out in an appropriate reaction vessel. When it is carried out under high pressure conditions, an autoclave can be used; when it is carried out under low pressure conditions, a normal pressure reaction vessel can be selected, or an autoclave can be used, and the pressure conditions can be controlled well.
[0030] The ruthenium single-atom alloy catalyst and the application method in plastic hydrogenolysis provided by the present invention can efficiently catalyze and convert plastic into high-value liquid fuel and lubricant base oil under a wide hydrogen pressure range (0MPa-6MPa) and low temperature (100-500°C) conditions. Moreover, during the hydrogenolysis process, the Ru at the single-atom site in the ruthenium single-atom alloy catalyst of the present invention controls the CC bond to break only once, thereby avoiding continuous bond breaking to produce more methane. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a schematic diagram of the crystal structure of the ruthenium single-atom alloy used in the present invention.
[0032] Figure 2 The Ru provided in Example 1 SA Electron microscopy image of Pt / C catalyst. DETAILED DESCRIPTION
[0033] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.
[0034] The crystal structure of the ruthenium single-atom alloy used in the present invention is as follows: Figure 1 As shown, green represents ruthenium atoms and gray represents the second metal atoms M.
[0035] Example 1
[0036] This embodiment provides a Ru with a loading of 20 wt%. 0.1 The Pt / C catalyst is prepared by the following steps:
[0037] Take 20mg Ru 0.1 Pt nanoparticles with a size of 4 nm were dissolved in toluene to obtain Ru 0.1 Pt solution (first solution);
[0038] 80 mg of activated carbon (Vulcan) was dispersed in toluene to obtain an activated carbon solution (second solution);
[0039] Will Ru 0.1 The Pt solution was added to the activated carbon solution, ultrasonicated for 1 hour, filtered and dried to obtain the Ru 0.1 Pt / C catalyst.
[0040] The Ru 0.1 Electron microscopy images of Pt / C catalysts Figure 2 As shown, Figure a is the Ru in the first solution 0.1 Electron microscopy image of Pt nanoparticles. Figure b is the Ru nanoparticles obtained after drying. 0.1Electron microscopy image of Pt / C catalyst, Figure c is Ru 0.1 Local electron microscopy image of Pt nanoparticles.
[0041] Depend on Figure 2 It can be seen that the 4 nm nanoparticles are uniformly dispersed on the carbon carrier, and the formed nanoparticle alloy is a uniform single crystal structure, indicating that Ru is uniformly dispersed in the nanoparticles in the form of single atoms.
[0042] This embodiment also provides a method based on the above Ru 0.1 The method for hydrogenolysis of plastics using a Pt / C catalyst comprises the following steps:
[0043] 40 mg of Ru 0.1 The Pt / C catalyst was mixed with 340 mg of LDPE, placed in an autoclave, and hydrogen was injected for hydrogenolysis. During the hydrogenolysis process, the stirring rate was 300 r / min, the reaction temperature was controlled at 300°C, the hydrogen pressure was normal pressure (0.1 MPa), and the reaction time was 24 hours. The test results of hydrogenolysis are shown in Table 1.
[0044] The conversion rate is calculated as follows:
[0045] Conversion rate = (mass of plastic before reaction - mass of plastic after reaction) / mass of plastic before reaction;
[0046] The methane selectivity is calculated as follows: methane selectivity = mass of methane / mass of all products after plastic conversion.
[0047] Comparative Example 1
[0048] This comparative example provides a plastic hydrogenolysis method, which is different from the plastic hydrogenolysis method provided in Example 1 in that the catalyst is Ru / C with a loading amount of 1 wt%, and the rest is the same as Example 1. The test results of hydrogenolysis are shown in Table 1.
[0049] Comparative Example 2
[0050] This comparative example provides a plastic hydrogenolysis method, which differs from the plastic hydrogenolysis method provided in Example 1 in that no catalyst is used, and the rest is the same as Example 1. The test results of hydrogenolysis are shown in Table 1.
[0051] Table 1
[0052] Example 1 Comparative Example 1 Comparative Example 2 catalyst <![CDATA[Ru 0.1 Pt / C]]> Ru / C No catalyst Conversion rate / % 100 28 5 Methane selectivity / % 3 35 32
[0053] It can be seen from Table 1 that the ruthenium single-atom alloy catalyst provided by the present invention can achieve the degradation of LDPE under low hydrogen pressure and low temperature conditions, and the conversion rate is significantly higher than that of the Ru / C catalyst. Moreover, the methane selectivity of Example 1 is much lower than that of Comparative Examples 1 and 2, indicating that the Ru in the catalyst of Example 1 can control the CC bond to break only once, thereby avoiding continuous bond breaking to produce more methane, thereby reducing the methane selectivity.
[0054] Example 2
[0055] This embodiment also provides Ru based on Example 1 0.1 The method for hydrogenolysis of plastics using a Pt / C catalyst comprises the following steps:
[0056] 40 mg of Ru 0.1 The Pt / C catalyst was mixed with 340 mg of PP, placed in an autoclave, and hydrogen was injected for hydrogenolysis. During the hydrogenolysis process, the stirring rate was 300 r / min, the reaction temperature was controlled at 300°C, the hydrogen pressure was normal pressure (0.1 MPa), and the reaction time was 24 hours. The test results of hydrogenolysis are shown in Table 2.
[0057] Comparative Example 3
[0058] This comparative example provides a plastic hydrogenolysis method, which is different from the plastic hydrogenolysis method provided in Example 2 in that the catalyst is Ru / C with a loading amount of 1 wt%, and the rest is the same as Example 2. The test results of hydrogenolysis are shown in Table 2.
[0059] Comparative Example 4
[0060] This comparative example provides a plastic hydrogenolysis method, which differs from the plastic hydrogenolysis method provided in Example 2 in that no catalyst is used, and the rest is the same as Example 2. The test results of hydrogenolysis are shown in Table 2.
[0061] Table 2
[0062] Example 2 Comparative Example 3 Comparative Example 4 catalyst <![CDATA[Ru 0.1 Pt / C]]> Ru / C No catalyst Conversion rate / % 100 21 4 Methane selectivity / % 1.5 34 21
[0063] It can be seen from Table 2 that the ruthenium single-atom alloy catalyst provided by the present invention can achieve PP degradation under low hydrogen pressure and low temperature conditions, and the conversion rate is significantly higher than that of the Ru / C catalyst. Moreover, the methane selectivity of Example 2 is much lower than that of Comparative Examples 3 and 4, indicating that the catalyst of Example 2 can significantly reduce the methane selectivity.
[0064] Example 3
[0065] This embodiment also provides Ru based on Example 1 0.1 The method for hydrogenolysis of plastics using a Pt / C catalyst comprises the following steps:
[0066] 40 mg of Ru 0.1 The Pt / C catalyst was mixed with 340 mg of HDPE, placed in an autoclave, and hydrogen was injected for hydrogenolysis. During the hydrogenolysis process, the stirring rate was 300 r / min, the reaction temperature was controlled at 300°C, the hydrogen pressure was 20 bar, and the reaction time was 0.1 hour. The test results of hydrogenolysis are shown in Table 3.
[0067] Comparative Example 5
[0068] This comparative example provides a plastic hydrogenolysis method, which is different from the plastic hydrogenolysis method provided in Example 3 in that the catalyst is Ru / C with a loading amount of 1 wt%, and the rest is the same as Example 3. The test results of hydrogenolysis are shown in Table 3.
[0069] Comparative Example 6
[0070] This comparative example provides a plastic hydrogenolysis method, which differs from the plastic hydrogenolysis method provided in Example 3 in that no catalyst is used, and the rest is the same as Example 3. The test results of hydrogenolysis are shown in Table 3.
[0071] Table 3
[0072] Example 3 Comparative Example 5 Comparative Example 6 catalyst <![CDATA[Ru 0.1 Pt / C]]> Ru / C No catalyst Conversion rate / % 100 41 4 Methane selectivity / % 1.5 42 32
[0073] It can be seen from Table 3 that the ruthenium single-atom alloy catalyst provided by the present invention can achieve the degradation of HDPE under low hydrogen pressure and low temperature conditions, and the conversion rate is significantly higher than that of the Ru / C catalyst. Moreover, the above conversion rate is obtained in a very short time. Moreover, the methane selectivity of Example 3 is much lower than that of Comparative Examples 5 and 6, indicating that the catalyst of Example 3 can significantly reduce the methane selectivity.
[0074] Example 4
[0075] This embodiment provides a Ru with a loading of 6.9 wt%. 0.3 The Co / C catalyst is prepared by the following steps:
[0076] Take 6.9 mg of Ru with a size of 8 nm 0.3 Co nanoparticles dissolved in toluene to obtain Ru 0.3 Co solution (first solution);
[0077] 93.1 mg of activated carbon (Vulcan) was dispersed in toluene to obtain an activated carbon solution (second solution);
[0078] Will Ru 0.3 The Co solution was added to the activated carbon solution, ultrasonicated for 1 hour, filtered and dried to obtain the Ru 0.3 Co / C catalyst.
[0079] This embodiment also provides a method based on the above Ru 0.3 The plastic hydrogenolysis method using a Co / C catalyst comprises the following steps:
[0080] 40 mg of Ru 0.3 The Co / C catalyst was mixed with 340 mg of PET, placed in an autoclave, and hydrogen was injected for hydrogenolysis. During the hydrogenolysis process, the stirring rate was 300 r / min, the reaction temperature was controlled at 300° C., the hydrogen pressure was normal pressure (0.1 MPa), and the reaction time was 24 hours. The test results of hydrogenolysis are shown in Table 4.
[0081] Comparative Example 7
[0082] This comparative example provides a plastic hydrogenolysis method, which is different from the plastic hydrogenolysis method provided in Example 4 in that the catalyst is Ru / C with a loading amount of 1 wt%, and the rest is the same as Example 4. The test results of hydrogenolysis are shown in Table 4.
[0083] Comparative Example 8
[0084] This comparative example provides a plastic hydrogenolysis method, which differs from the plastic hydrogenolysis method provided in Example 4 in that no catalyst is used, and the rest is the same as Example 4. The test results of hydrogenolysis are shown in Table 4.
[0085] Table 4
[0086] Example 4 Comparative Example 7 Comparative Example 8 catalyst <![CDATA[Ru 0.3 What / C]]> Ru / C No catalyst Conversion rate / % 100 18 4 Methane selectivity / % 2.1 21 15
[0087] It can be seen from Table 4 that the ruthenium single-atom alloy catalyst provided by the present invention can achieve PET degradation under low hydrogen pressure and low temperature conditions, and the conversion rate is significantly higher than that of the Ru / C catalyst. Moreover, the methane selectivity of Example 4 is much lower than that of Comparative Examples 7 and 8, indicating that the catalyst of Example 4 can significantly reduce the methane selectivity.
[0088] Example 5
[0089] This embodiment provides a Ru with a loading of 7.2 wt%. 0.2 The Ni / C catalyst is prepared by the following steps:
[0090] Take 7.2 mg of Ru with a size of 7 nm 0.2 Ni nanoparticles dissolved in toluene to obtain Ru 0.2 Ni solution (first solution);
[0091] 92.8 mg of activated carbon (Vulcan) was dispersed in toluene to obtain an activated carbon solution (second solution);
[0092] Will Ru 0.2The Ni solution was added to the activated carbon solution, ultrasonicated for 1 hour, filtered and dried to obtain the Ru 0.2 Ni / C catalyst.
[0093] This embodiment also provides a method based on the above Ru 0.2 The method for hydrogenolysis of plastics using a Ni / C catalyst comprises the following steps:
[0094] 40 mg of Ru 0.2 The Ni / C catalyst was mixed with 340 mg of PET, placed in an autoclave, and hydrogen was injected for hydrogenolysis. During the hydrogenolysis process, the stirring rate was 300 r / min, the reaction temperature was controlled at 300° C., the hydrogen pressure was normal pressure (0.1 MPa), and the reaction time was 24 hours. The test results of hydrogenolysis are shown in Table 5.
[0095] Comparative Example 9
[0096] This comparative example provides a plastic hydrogenolysis method, which is different from the plastic hydrogenolysis method provided in Example 5 in that the catalyst is Ru / C with a loading amount of 1 wt%, and the rest is the same as Example 5. The test results of hydrogenolysis are shown in Table 5.
[0097] Comparative Example 10
[0098] This comparative example provides a plastic hydrogenolysis method, which differs from the plastic hydrogenolysis method provided in Example 5 in that no catalyst is used, and the rest is the same as Example 5. The test results of hydrogenolysis are shown in Table 5.
[0099] Table 5
[0100] Example 5 Comparative Example 9 Comparative Example 10 catalyst <![CDATA[Ru 0.2 By / C]]> Ru / C No catalyst Conversion rate / % 100 18 4 Methane selectivity / % 2.3 21 15
[0101] It can be seen from Table 5 that the ruthenium single atom alloy catalyst provided by the present invention can achieve PET degradation under low hydrogen pressure and low temperature conditions, and the conversion rate is significantly higher than that of the Ru / C catalyst. Moreover, the methane selectivity of Example 5 is much lower than that of Comparative Examples 9 and 10, indicating that the catalyst of Example 5 can significantly reduce the methane selectivity.
Claims
1. A ruthenium single-atom alloy catalyst, comprising a ruthenium single-atom alloy and a carrier, wherein: The general formula of the ruthenium single atom alloy is: Ru SA M, wherein M is selected from one or a combination of two or more of Pt, Pd, Fe, Co, Ni, Cu, Zn, Mg, Ca, and Mn; Among them, the value of SA is 0.01-1.
2. The ruthenium single-atom alloy catalyst according to claim 1, wherein Taking the mass of the ruthenium single-atom alloy catalyst as 100%, the loading amount of the ruthenium single-atom alloy is 1wt%-50wt%, preferably 1wt%-20wt%, and more preferably 5wt%-20wt%.
3. The ruthenium single-atom alloy catalyst according to claim 1, wherein The carrier is selected from one or a combination of two or more of a carbon-based carrier, a metal oxide carrier and a metal nanoparticle carrier; Preferably, the carbon-based carrier is selected from one or a combination of two or more of Norit, Ketjen Black, Vulcan, Black Pearl, acetylene black, carbon nanotubes, graphene, carbon nitride, nitrogen-doped carbon, molybdenum carbide, and iron carbide; Preferably, the metal oxide in the metal oxide carrier is selected from one or a combination of two or more of cerium oxide, zinc oxide, aluminum oxide, zirconium oxide, magnesium oxide, molybdenum oxide, and tungsten oxide; Preferably, the metal in the metal nanoparticle carrier is selected from one or a combination of two or more of platinum, gold, silver, ruthenium, rhenium and palladium.
4. The method for preparing the ruthenium single-atom alloy catalyst according to any one of claims 1 to 3, comprising the following steps: Dispersing ruthenium single-atom alloy nanoparticles in a first solvent to obtain a first solution, and dispersing the carrier in a second solvent to obtain a second solution; preferably, the particle size of the ruthenium single-atom alloy nanoparticles is 2nm-20nm; The first solution and the second solution are mixed, and then subjected to ultrasound, filtration and drying to obtain a ruthenium single-atom alloy catalyst.
5. A method for hydrogenolysis of plastics, which is carried out using the ruthenium single-atom alloy catalyst according to any one of claims 1 to 3; the method for hydrogenolysis of plastics comprises the following steps: The plastic is mixed with the ruthenium single atom alloy catalyst and placed in a hydrogen environment for hydrogenolysis.
6. The method for hydrogenolysis of plastics according to claim 5, wherein: The mass ratio of the plastic to the ruthenium single-atom alloy catalyst is 0.01-2.0 g: 4-40 mg.
7. The method for hydrogenolysis of plastics according to claim 5, wherein: The hydrogen pressure of the hydrogen environment is 0MPa-6MPa.
8. The method for hydrogenolysis of plastics according to claim 5, wherein: The hydrogen pressure of the hydrogen environment is lower than 1 MPa.
9. The method for hydrogenolysis of plastics according to claim 5, wherein: The temperature of the hydrogenolysis is 100°C-500°C.
10. The method for hydrogenolysis of plastics according to claim 5, wherein: The plastic includes one or a combination of two or more of low-density polyethylene, linear low-density polyethylene, high-density polyethylene, polypropylene, polystyrene, polyvinyl chloride, polyethylene terephthalate, polylactic acid, polycaprolactone, polycarbonate, nylon 66, polybutylene terephthalate, and polyurethane.